Exchange Rate Volatility, Stock Prices Movement and Aggregate Output in Nigeria - Adeoti, Julius Olakunle; Adebis, Dauda Gbolagade (Advances in Social Sciences Research Journal, 2018)
The paper examined the causal relationship among exchange rate volatility, stock prices movement and aggregate output in Nigeria from 1986 to 2014. The study used ARDL Bound test cointegration approach to establish long run relationship and Vector Error Correction Model (VECM) to examine the short and long run causal relationship among the variables. The results showed that there was long run relationship among exchange rates volatility, stock prices movement and real GDP. Furthermore, a unidirectional causality was observed between aggregate output and stock prices movement in the short run, while in the long run, a bi-directional causal relationship was established. However, the study could not detect, either in the short or long run, any causality from exchange rate volatility to either stock prices movement or real GDP and vice versa. In this regard, more efforts should be geared towards financial market development, while less attention should not be paid to exchange rates stability.